A MODERN VIEW ON THE RELEVANCE OF HYPOTHYROIDISM PREVENTION - Pokiza Khusanovna Azizova; Nafisakhon V. Tursunaliyeva; Marjona U. Abdullajonova (Web of Journals Publishing, 2025)
Hypothyroidism is a common endocrine pathology that occurs against the background of a long-term reduced concentration of hormones produced by the thyroid gland. It is manifested by a decrease in the functions of the thyroid gland and a sharp decrease in the amount of hormones produced by it. Since thyroid hormones have a direct impact on many physiological processes in the body, this disease manifests itself in various organs and systems. This leads to metabolic disorders, and then to complications in the heart, blood vessels, nervous and reproductive systems. The disease occurs against the background of a slowdown in all processes in the body. The person feels weak and sleepy. A common complication is excess weight gain.
Keywords: Hypothyroidism, autoimmune thyroiditis, TSH, thyroid hormones, prevention.